Taxonomic review of the leafhopper genus Aconurella Ribaut (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) from Pakistan with description of three new species - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2018)
The genus Aconurella Ribaut from Pakistan is reviewed with three new species, A. paraerebus sp. n., A. choui sp. n. and A. naranensis sp. n. described and illustrated in this paper. A key to Pakistani species of the genus is also given.